Conversion of whey and other dairy waste into antimicrobial and immunoregulatory compounds by fermentation - Michael H. Tunick; John A. Renye; Rafael A. Garcia (Frontiers in Food Science and Technology)
Fermentation by lactic acid bacteria has been used for millennia to preserve food and make it more palatable. These microorganisms may also generate bioactive compounds with the potential to serve as components in active edible food packaging or as alternative therapeutics. Dairy waste products, especially whey, provide a substrate for growth of these bacteria, and can be incorporated into the formulations of edible food packaging. This minireview deals with the use of dairy waste to grow lactic acid bacteria to produce bioactive compounds, specifically antimicrobial peptides and immunoregulatory molecules, and their potential use in food and therapeutic applications.